'A little piece of my heart goes with each of them': Foster carer reflections on current fostering practice. (December 2022) - Blackburn, Carolyn; Matchett, Elaine
In the UK, fostering is the principal way of looking after children in care. Foster carers have been reported to be motivated to undertake this task by an intrinsic desire to nurture and improve the lives of young people. However, the work faces numerous challenges, especially with regard to relationships with other professionals involved in children's lives and a lack of support for young people with complex needs. Allegations made against carers also increase the potential for carer stress and an exit from fostering. This article reports the findings from an online survey of 422 foster carers in England, complemented by eight in-depth interviews. Although this research was undertaken during the global Covid-19 pandemic when schools and other social settings were closed for prolonged periods, which had some effect on participants' responses, the issues raised were enduring rather than ephemeral. The findings highlight the two key themes of 'transformative professional relationships' and 'translations of professional love'. Recommendations for professional training across disciplines are suggested.